2022
DOI: 10.1055/a-1911-3326
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cannabis Use during Pregnancy on Low Birth Weight and Preterm Birth: A Systematic Review and Meta-analysis

Abstract: Objective: to summarize literature regarding the effects of cannabis use during pregnancy on low birthweight (LBW), preterm birth (PTB) and small for gestational age (SGA). Study Design: systematic review and meta-analysis. A literature search was conducted in PubMed, Scopus, EBSCO and Web of Science in May 2021 and updated in November 2021. Only studies that assessed the isolated use of cannabis during pregnancy, controlling for cigarette smoking and other illicit drug use, were included. Data was synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…This limitation is particularly important in interpreting the results for individuals who use both nicotine and cannabis. Our estimated OR for cigarette use might be overestimated, given the reported associations of cannabis use with SGA and low birth weight . Seventh, we dichotomized e-cigarette and cigarette use (use vs nonuse) due to limited sample sizes of the original frequency categories.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation is particularly important in interpreting the results for individuals who use both nicotine and cannabis. Our estimated OR for cigarette use might be overestimated, given the reported associations of cannabis use with SGA and low birth weight . Seventh, we dichotomized e-cigarette and cigarette use (use vs nonuse) due to limited sample sizes of the original frequency categories.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive strategies were divided into the 10 following categories: midwifery care, health promotion programs for smoking cessation, alcohol reduction during pregnancy, folic acid, vitamin D, iron, and zinc supplementation, a well-balanced diet, COVID-19 vaccination and cannabis use during pregnancy. The most significant and high-quality publications focusing on preventive strategies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in a randomized controlled trial carried out by Higgins et al, it was shown that financial incentives added to Best Practice increase smoking cessation among not only antepartum, but also postpartum women, were reducing the risk of SGA and potential adverse outcomes [ 30 , 74 ]. A systematic review and meta-analysis conducted by Baía et al showed that using cannabis by pregnant women appeared to increase the risk of SGA [ 31 ]. Alcohol consumption is also linked with adverse perinatal outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…In recent large systematic reviews, prenatal cannabis use was associated with greater odds of preterm birth, smallfor-gestational-age, and perinatal mortality even after accounting for prenatal tobacco use. 71,72 THC crosses the placenta and can result in fetal blood levels of THC comparable to maternal blood levels. 73 The fetal ECS plays a key role in regulating and signaling the embryonic development of neural cells in functional areas such as the forebrain and hippocampus.…”
Section: Risk During Pregnancymentioning
confidence: 99%